A critical analysis of fiscal stability agreements as offered in the tenth schedule of the income tax act for energy companies in South Africa in light of recent oil and gas finds in South Africa - Melapi, Babalwa Melapi (Department of Finance and Tax, 2022)
South Africa remains reliant on a number of countries to sustain its energy requirements. The acute shortage and unreliable supply of electricity, requires that South Africa consider other energy sources, more specifically, that it considers the use of oil and gas as an alternative or complementary energy source to the main energy sources currently used in the country. The recent announcement of oil and gas discoveries in South Africa could see less reliance on other countries for the importation of crude oil and petroleum products. Despite newly discovered oil and gas resources in South Africa, the country will continue to remain reliant on the industry's international investors since South Africa does not have the requisite expertise, skill and capital to operate efficiently in this industry. The shortage of capital to further develop the industry means that the country will need to continue to compete with other emerging markets to secure international investment. One such way of being an attractive investment destination has been touted through the offering of a tax regime with incentives which, more importantly, provides certainty and stability (Mausling, 2017: iv). South Africa introduced the Tenth Schedule to the Income Tax Act No.58 of 1962 (“Income Tax Act”) which aims to provide incentives that stimulate industrial and economic growth in the oil and gas industry. Against the backdrop of recent oil and gas finds, the Minister of Finance announced in the 2019 Budget Speech that changes to the Tenth Schedule would be considered. This has brought about the need to consider the role of fiscal stability agreements (“FSA”). Under the Tenth Schedule, South Africa offers FSAs which allows for the “freezing” of the Income tax provisions when the FSA was signed i.e. even if there is a new tax regime, the investor may elect to continue to use the old tax regime. Firstly, this dissertation considers whether there is a need for FSAs. To achieve this aim, the dissertation considers the reasons for fiscal instability and considers these within the South African context. These reasons are used to substantiate whether there is a need for FSA's as a remedy for fiscal instability. The current incentives offered by the Tenth Schedules are examined in order to determine the reasons as to why oil and gas companies would find FSAs advantageous. Secondly, the dissertation examines the types of FSAs typically offered, including freezing clauses (currently used in the FSA offered by South Africa), economic balancing clauses and, finally, hybrid clauses. In critically reviewing these different clauses, the most preferred clause is suggested. A further review of this preferred clause is enhanced through the consideration of the types of FSAs offered by comparable countries. Ghana and Mozambique have been identified and selected for comparison for the purposes of this study. The paper further considers aspects of the FSA such as the legality and legal effectiveness of FSAs. Such issues are critical in light of the challenges that have been identified in the use of FSAs, particularly that such instruments limit the State's sovereignty. Furthermore, the costs associated with FSAs are considered. Lastly, the remedies available should the state elect not to adhere to a FSA once in force are considered. The findings of the study suggest that there remains a need for FSAs in South Africa. However, the findings indicate a need to change the current fiscal stability clause into an economic balancing clause, in particular a negotiated economic balancing clause.